Quality of Mayonnaise Supplemented with Calamansi Peel Flour (Citrofortunella microcarpa) as a Potential Functional Food - Afifah, Najla; Kartikasari, Lilik Retna; Nuhriawangsa, Adi Magna Patriadi (Buletin Peternakan, 2025)
This study aims to evaluate the physicochemical properties and consumer preferences of mayonnaise containing calamansi peel flour (Citrofortunella microcarpa) as a functional food ingredient. It used a completely randomized design (CRD) with four treatments: 0% (P0), 1.5% (P1), 3.0% (P2), and 4.5% (P3), each consisting of six replications. The observed parameters included antioxidant activity (DPPH, total phenolics), physical properties (pH, viscosity), and chemical properties (moisture, ash, protein, fat, carbohydrate, crude fiber content), as well as consumer preferences assessed through a hedonic test. The IC50 value for the antioxidant activity of calamansi peel flour was 723.92 ppm, while the total phenol content was 10.36 mg GAE/g. Increasing the level of calamansi peel flour raised the viscosity, moisture, ash, protein, carbohydrate, and crude fiber content of mayonnaise, but it decreased the fat content. In conclusion, the addition of 1.5% calamansi peel flour produces the finest quality mayonnaise and is regarded as acceptable by consumers as a functional food component.